Developing and Validating a New Wireless Wearable Device for Balance Measurement in Sport and Clinical Setting - Mohammad Maleki; Mehran Faqihsolimani; Behzad Mortezazadeh (Annals of Applied Sport Science)
One of the new clinical techniques to assess the lower body parameters is the wearable ultrasonic sensors. The device which can measure the static and dynamic balance abilities in sport and clinical setting by the traveled signals of ultrasonic transmitter and receiver between two feet was developed and validated. The new device consisted of a pressure gauge and a digital centimeter indicator and examined the tests in two balanced states of Stork and Y dynamic. First, 210 participants were selected based on convenience sampling. Then, using the new ultrasonic balance device, all samples took each test conducted by the Stork and Y dynamic tests for3 times. The results showed high reliability between the data of static and dynamic balances obtained from the ultrasonic device and through the methods of Stork and Y (the SEBT modified version) (r=0.90; r=0.92). The inter-rater reliabilities of the three-time conduction of the stork and Y dynamic tests were found to be very high (ICC=0.92; ICC=0.91). The ultrasonic balance device was both valid and reliable in measuring the Stork and Y dynamic balance tests. The new device could solve that defects associated with traditional stork and Y dynamic tests.